Optimizing Clinical Reasoning: Unpacking the Impact of Virtual Patient Educational Duration in Cancer Care and Nursing Students’ Experiences - Masoud Bahrami; Arash Hadadgar; Masoumeh Fuladvandi (Iranian Journal of Nursing and Midwifery Research)
Background: Teaching clinical reasoning to nursing students is essential for professionalizing and improving cancer patient care. This study investigates how training duration with Virtual Patients (VPs) impacts clinical reasoning and learners’ evaluation of their experiences. Materials and Methods: The present semi-experimental study was conducted with a pretest–post-test design and a control group. Through the census sampling method, 74 nursing students from Isfahan University of Medical Sciences, Iran, (in their 4th and 5th semester) who had taken the cancer course were selected (2019-2022) and, upon obtaining their consent, were enrolled in the study. The study began with a pretest, followed by engagement in five VP scenarios over 6 weeks, which was followed by the post-test phase. Data were collected via 23-item tests and the Huwendiek Questionnaire. The collected data were analyzed in SPSS software using correlation tests and t-tests. Results: The outcomes revealed a noteworthy disparity between the mean scores recorded in the pre-test and post-test stages after training, for both the 4th and 5th semester cohorts (p ≤ 0.001). Moreover, a notable discrepancy surfaced between the duration of training with VPs and the average post-test score (p ≤ 0.001). The correlation coefficient, for the 4th semester, stood at 0.65, while for the 5th semester, it was 0.213. Notably, the participants exhibited contentment with the learning experience through VPs. Conclusions: The survey found that 85.60% of participants prefer using VPs for clinical reasoning education. Our study underscores the link between the duration of VP interaction and improved clinical reasoning skills in nursing students.